Decode-and-forward relaying in mixed η − μ and gamma–gamma dual hop transmission system - Sharma, Nikhil; Bansal, Ankur; Garg, Parul (IET communications, 2016)
In this study, the authors carry out the performance analysis of an asymmetric dual hop relay system composed of both radio-frequency (RF) and free-space optical (FSO) links. The RF link is subject to generalised η − μ distribution, while the channel for FSO link is modelled as gamma–gamma distribution. The decode-and-forward relaying phenomena is used, where the relay decodes the received RF signal from the source and converts it into an optical signal using the sub-carrier intensity-modulation (SIM) scheme for transmission over the FSO link. The FSO link is subjected to pointing errors and account for both types of detection techniques, i.e. IM/DD and heterodyne detection. Novel exact closed-form expressions for the probability density function and cumulative distribution function of the equivalent end-to-end signal-to-noise ratio of the mixed RF/FSO system in terms of Meijer's G function are derived. Capitalising on these derived channel statistics, they provide the new closed-form expressions of outage probability and the ergodic channel capacity. They also provide the average bit-error rate for different binary modulations. Furthermore, the Monte Carlo simulations validate the analytical results.